Telemedicine for patients with rheumatic and musculoskeletal diseases during the COVID-19 pandemic; a positive experience in the Netherlands - Bos, Wouter H. (Rheumatol Int, 2021)
To describe the delivery of care for patients with rheumatic and musculoskeletal diseases (RMDs) from the perspective of rheumatologists in the Netherlands during the first months of the COVID-19 pandemic. A mixed methods design was used with quantitative and qualitative data from a cross-sectional survey sent to all members of the Dutch Rheumatology Society in May 2020. The survey contained questions on demographics, the current way of care delivery, and also on usage, acceptance, facilitators and barriers of telemedicine. Quantitative data were analyzed descriptively. The answers to the open questions were categorized into themes. Seventy-five respondents completed the survey. During the COVID-19 pandemic, continuity of care was guaranteed through telephone and video consultations by 99% and 9% of the respondents, respectively. More than 80% of the total number of outpatient visits were performed exclusively via telephone with in-person visits only on indication. One-quarter of the respondents used patient reported outcomes to guide telephone consultations. The top three facilitators for telemedicine were less travel time for patients, ease of use of the system and shorter waiting period for patients. The top three barriers were impossibility to perform physical examination, difficulty estimating how the patient is doing and difficulty in reaching patients. During the COVID-19 epidemic, care for patients with RMDs in the Netherlands continued uninterrupted by the aid of telemedicine. On average, respondents were content with current solutions, although some felt insecure mainly because of the inability to perform physical examination and missing nonverbal communication with their patients. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s00296-020-04771-6.